Studi Kausal Komparatif: Pembelajaran IPA Menggunakan Model Problem Based Learning terhadap Literasi Lingkungan dan Komunikasi Sains Siswa SMK Inisial X Pekanbaru (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to analyze the influence of the Problem Based Learning (PBL) model in science education on students’ environmental literacy and science communication skills at SMK Negeri 3 Pekanbaru, focusing on the topic of disaster mitigation. The research employed a causal comparative approach with a post-test only design, comparing two student groups: an experimental class using the PBL model and a control class using conventional teaching. The results revealed a significant difference in environmental literacy, with the experimental class achieving a higher average score (81.86) compared to the control class (62.05). This indicates that the PBL model is effective in enhancing students' understanding, awareness, and environmentally responsible behavior. The PBL approach encourages active student engagement and the application of knowledge to real-world scenarios, which is particularly beneficial in the context of environmental issues and disaster mitigation. By working through problems related to environmental challenges, students are likely to gain a deeper understanding of the topic, which fosters a sense of responsibility towards environmental sustainability. In terms of science communication, although the experimental class showed a higher average score (75.78) than the control class (72.92), the difference was not statistically significant. This may be due to a lack of intensive training in scientific discussions and presentations. While PBL encourages collaborative problem-solving and idea-sharing, students may still require more structured practice in presenting and communicating their findings clearly and persuasively. The integration of more structured activities focusing on science communication skills could further enhance the effectiveness of the PBL model. Overall, the PBL model demonstrates positive potential in improving both environmental literacy and science communication. However, to achieve its full impact, its implementation must be consistent, with a focus on providing students with additional opportunities to develop their communication skills.